Inovasi Pelayanan Perpustakaan Keliling Sebagai Media Revolusi Mental di Jawa Barat - Halimatus Sahdiyah Harahap; Bisyarah Rahmadhani; Afista Dwi Wardhani; Muhammad Ghifar Hawary; Akbar Ardianto Rukmana (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
This study aims to determine the quality of mobile library service which is one of the innovative services in the field of literacy organized by the Government of West Java. Literacy Program is an effort made to prepare human resources to realize the internalization of a mental revolution to face the demographic bonuses in West Java. Consequently, the local government of West Java in collaboration with DISPUSIPDA released several literacy programs, one of the programs is mobile library which includes all districts and cities in West Java. The method in this study uses a descriptive method with a qualitative approach. The data collection technique is done through data that is directly observed in the field (observation) and through interviews. From the result of the study found that service is effective and able to run well. This mobile library service is expected to be able to foster public interest in reading, especially students in West Java to support the demographic bonus in which it shapes the character of students in accordance with the concept of mental revolution which includes work ethic, integrity and mutual cooperation.